Aepytus (Pseudolaca) serta (Schaus) CURUBA STEM BLOWER - ROJAS DE HERNÁNDEZ, MARTHA; CHACÓN DE ULLOA, PATRICIA (Revista Colombiana de Entomología, 1980)
One of the main problems of the "curuba" crop (Passiflora mollisima Bailey), is the stemborer, Aepytus serta (Lepidóptera: Hepialidae), which was found in the Cauca Valley (Colombia) Feeding habits, relation to host plant, and main morphological characteristics for this species are described herein.